Profiles of major glucosinolates in different parts of white cabbage and their evolutions during processing into vegetable powder by various methods - Kuljarachanan, T. (2021)
Commercially discarded portions, i.e., outer leaves and core, as well as edible leaves, of white cabbage (Brassica oleracea L. var. capitata) were processed into vegetable powder rich in glucosinolates (GLSs). Four GLSs, i.e., sinigrin, glucoraphanin, glucoerucin, and glucobrassicin, were quantified in both fresh and processed samples. Fresh outer leaves and core contained higher GLSs contents comparable to edible leaves. Steam blanching, microwave-assisted blanching and ultrasound-assisted blanching were tested prior to hot air drying at 80°C to inhibit polyphenol oxidase, peroxidase, and myrosinase, which is the endogenous enzyme responsible for the degradation of GLSs during processing. Steam blanching for 3 min was eventually selected as it required the shortest time and had minute effect on GLSs. Drying caused significant reduction in GLSs contents. Glucobrassicin was noted to be the most heatsensitive, while glucoraphanin was the most heat-stable. GLSs content in vegetable powder was approximately 82 - 84% of those in the fresh samples.